A Security Framework for Railway Platform Development (International Journal of Scientific Research in Science and Technology, 2024)
The different modes of transport are air, water, and land transport, in which land transport includes rail transport, road transport and off-road transport. Most commonly using transport system are Roadways, Railways and Airways. In these frequently we use the railways, because it is cheaper and it is more convenient than other transport systems. The third largest railway network in the world is Indian railway network. But the accident’s occurs in the railways is higher. Mostly the accidents in the railway station occur between the railway platform and to the train, because of the platform gap. The platform gap is the gap exists between the train and to the platform. To avoid these accidents that the Indian government come with an indicative to increase the height of the platform. But it is not easy job to increase the height. At the time of working we cannot access the platforms. By applying my project it is easy to avoid the accidents as well as we can use the platform too. A human fall down in the gap exist between the platform and to the train can be totally avoided by introducing Mechanical platform edge extensions known as platform gap fillers which is used to bridge the gap between platform and to the train. This is more useful in the case of safeguard the human life and also it is cheaper than the cost which is involved for increase the height of the platform. In this regard the safety barrier setup present at the bottom of the platform will be automatically uplifted with the help of sensor, so the platform gap is closed with the safety barrier. And then it will retract again into the bottom at the platform after leaving the station. By this project the platform gap accidents can be avoided.
Keywords: Arduino UNO; Servo Motor; Ultrasonic Sensor